A Study on the Current Situation and Development Strategies of Integrating the Deep Learning Concept into the Quality Management System of International Chinese Language Education in Indonesian Primary and Secondary Schools - Julianti; Zhang Hao; Cindy Claudia Linnardi; Yanti; Yelly Christiani (Riviera Publishing, 2026)
In response to the era requirements of educational transformation driven by Indonesia's National AI Strategy 2045 and Guidelines for the Implementation of Deep Learning, and to address the adaptation dilemma between the quality management system of Chinese language education in Indonesian primary and secondary schools and the deep learning orientation, this study adopted a mixed research method to conduct questionnaires and interviews with persons in charge of Chinese language teaching in primary and secondary schools across seven core cities of Indonesia. The findings reveal that the scores of Indonesian Chinese language education quality management in the five dimensions of curriculum, teaching staff, assessment, resources and management all fall in the low range of 1.57-1.86, presenting an overall characteristic of “initial establishment of basic functions and insufficient systemic effectiveness”, and showing a significant gap with the active construction, situational transfer and higher-order thinking development emphasized by deep learning. Based on the